PROFIL KOMPETENSI GURU BIMBINGAN DAN KONSELING DALAM PELAYANAN KELOMPOK DI SMA SUMATRA BARAT - Fitria Kasih, M.Pd Kons (Universitas PGRI SUMATERA BARAT, 2017)
The purpose of this study was to describe: (1) Teachers of Guidance and Counseling Competence seen from the service formation phase in group (2) Teachers of Guidance and Counseling Competence seen from the service transitional in group, (3) Teachers of Guidance and Counseling Competence seen from the service phase activity in group, (4) Teachers of Guidance and Counseling Competence seen from the service ending phase in group. This study was descriptive qualitative approach. The informants were teachers of Guidance and Counseling as the leader of the group, group members, and coworkers’ group leader. The instruments were interview and documentation study. Technique of data analysis was data reduction, data presentation and conclusion inductively. The results of the study were (1) Phase of formation has not focus on the explanation of the activities purpose towards the growing sense to know each other among the group members, (2) Phase of transition has not been confirmed to move on the next phase, (3) Phase of activity has not been demonstrated as a regulator in this activity, and yet liven in group, (4) Phase of ending did not really understand that the group members can commit to either, yet the conclusion of this activity. The Implication is teachers of Guidance and Counseling obviously need to improve their competence in service groups according to the phases of group services.